Diet, exercise, obesity, smoking and alcohol consumption in cancer survivors and the general population: a comparative study of 16 282 individuals - Wang, Z (Br J Cancer, 2015)
BACKGROUND: Cancer survivors may be particularly motivated to improve their health behaviours. METHODS: We compared health behaviours and obesity in cancer survivors with the general population, using household survey and cancer registry data. RESULTS: Cancer survivors were more likely than those with no history of cancer to eat fruit and vegetables (OR(adj) 1.41, 95% CI 1.19–1.66), less likely to engage in physical activity (OR(adj) 0.79, 95% CI 0.67–0.93) and more likely to have stopped smoking (OR(adj) 1.25, 95% CI 1.09–1.44). CONCLUSIONS: Most health-related behaviours were better in cancer survivors than the general population, but low physical activity levels may be amenable to health promotion interventions.